PENGEMBANGAN WISATA BAHARI PANTAI KARANG JAHE DALAM MENDUKUNG PEMBANGUNAN LINGKUNGAN BERKELANJUTAN - Julita Budi Prasetyo; Fuad Muhammad; Denny Nugroho Sugianto (IST AKPRIND Yogyakarta, 2018)
Coastal ecosystems are dynamic ecosystems and biodiversity, both on land and at sea, and interact between these habitats. But behind its great potential, coastal areas are vulnerable to the impact of human activities. Development activities, in general, directly and indirectly have an adverse impact on coastal ecosystems. In addition to biodiversity, coastal areas also have resource productivity and environmental services as well as accessibility. In these conditions, the coastal region finds its relevance as a potential place for the development of various development activities intensively. However, on the other hand, it is also very vulnerable to various forms of negative impacts caused by development activities both within the coastal areas and those on the upper and the high seas. Thus, the fundamental and critical challenge for the coastal area planners and managers is how to facilitate economic development, while minimizing the negative impacts of development activities in accordance with the carrying capacity of the coastal environment. Coastal tourism becomes one potential alternative that can be developed. This article aims to examine the development of marine ecotourism in support of sustainable development. This study takes place in the tourist area of ​​Karang Jahe Beach, Rembang Regency. The study was conducted qualitative descriptive based on existing literature studies. Studies show that natural resource-based tourism activities, including marine tourism, are tools to support sustainable development. The growth of ecotourism activities promotes economic growth and community welfare and conservation of natural resources.